Duck Egg Shell and Bay Leaf Extracts (Syzygium polyanthum [Wight] Walp.) Toothpaste Development Using Sodium CMC as a Binder - ERYANI, MIKHANIA; perwita, tista; aditama, agnis; rashati, dewi; husni, patihul; wijiani, nina (Pharmaceutical Journal of Indonesia, 2026)
Background: Toothpaste is a semi-solid preparation that helps shield teeth from bacterial harm by including abrasive compounds and other helpful elements. Duck eggshells are one of the natural materials that contain calcium carbonate as an abrasive, while bay leaves are a plant that hassantibacterial properties. Objectives: This study aims to formulate duck egg shell toothpaste and bay leaf extract (Syzygium polyanthum [Wight] Walp.) with sodium CMC variation concentrations. Methods: toothpaste is formulated with variation CMC concentration are 3% for F1; 4.5% for F2; and 6% for F3 and evaluate its physical properties. The physical properties tests conducted included organoleptic tests, homogeneity, pH, viscosity, spreadability, and foam height. Results: From the research results, there is an effect of varying sodium CMC concentrations on the physical properties of pH, viscosity, spreadability, and foam height, but no effect of varying sodium CMC concentrations on the organoleptic and homogeneity properties. Conclusions: The research indicate that all formulas meet the requirements for the physical property tests of duck egg shell toothpaste and bay leaf extract.